2002
DOI: 10.1002/jmv.2172.abs
|View full text |Cite
|
Sign up to set email alerts
|

Latent infection of human herpesvirus 6 in astrocytoma cell line and alteration of cytokine synthesis

Abstract: In order to study the pathogenesis of HHV-6 infection in central nervous system disorders, U251 cell line was infected with freshly isolated variant B HHV-6. Although IEA/ex 3 antigen (immediate early protein) was detected in infected cell nuclei, neither the presence of OHV-3 antigen (late antigen) nor production of infectious virus was demonstrated. These results indicate that abortive infection was established in the cells. After viral infection, the viral genome copy in the infected cells gradually decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Primary human astrocytes derived from a single brain are difficult to propogate in large quantities and grow slowly, and insufficient quantities are available to extensively investigate. As a result, we utilized the established model system of GFAP-positive U251 glioma cells that has been used to study HHV-6 (Akhyani et al 2006;Yoshikawa et al 2002) to confirm that the characteristics of HHV-6 infection and dysregulation of glutamate would mimic our observations in primary astrocytes.…”
Section: Hhv-6a Actively Infects Primary Human Astrocytesmentioning
confidence: 51%
“…Primary human astrocytes derived from a single brain are difficult to propogate in large quantities and grow slowly, and insufficient quantities are available to extensively investigate. As a result, we utilized the established model system of GFAP-positive U251 glioma cells that has been used to study HHV-6 (Akhyani et al 2006;Yoshikawa et al 2002) to confirm that the characteristics of HHV-6 infection and dysregulation of glutamate would mimic our observations in primary astrocytes.…”
Section: Hhv-6a Actively Infects Primary Human Astrocytesmentioning
confidence: 51%
“…2B, lanes 3 and 5) similar to reactivation effects previously reported by others. 23 Initial results of Western blot analyses also suggest an inhibitory effect of ART on HHV-6B (strain Z29) early/late protein synthesis (data not shown).…”
Section: Sensitivity Of Hhv-6a To Artmentioning
confidence: 83%
“…39,40 Although IL-6 synthesis does not increase in HHV-6-infected PBMCs, 39 we observed the enhanced production of this cytokine in a virally infected neuroglial cell line. 41 Furthermore, elevated IL-6 levels have been observed in HHV-6-infected patients that exhibit frequent seizures. 42 Recent microarray analyses have demonstrated that the transcription of mRNA encoding inflammatory cytokines was upregulated in virally infected cells.…”
Section: Discussionmentioning
confidence: 99%